(untitled) (Law Research Review Quarterly, 2026)
Forced delisting is a measure taken by the Indonesia Stock Exchange to remove the shares of issuers that no longer meet the requirements for being listed, one of which is due to default. This situation has the potential to cause losses for investors due to the loss of stock liquidity and a reduced opportunity to recover their investment value. One form of legal protection provided to investors is the share buyback mechanism, as stipulated in POJK Number 3/POJK.04/2021. However, in practice, buybacks are often not optimally implemented because issuers experiencing default are generally in financial distress. This study aims to analyze investor legal protection against the impact of forced delisting due to default and examine the obstacles and efforts to optimize buyback implementation in the Indonesian capital market. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a case study approach through an analysis of the case of PT Sri Rejeki Isman Tbk (Sritex). The research results indicate that legal protection for investors is stipulated in Law Number 8 of 1995 concerning Capital Markets, Law Number 40 of 2007 concerning Limited Liability Companies, and OJK Regulation Number 3/POJK.04/2021. However, the effectiveness of this protection is not optimal because buyback obligations are highly dependent on the issuer’s financial capacity. This situation creates a gap between normative regulations and their implementation and results in investors lacking legal certainty when buybacks cannot be implemented. Therefore, regulatory improvements are needed to establish alternative protection mechanisms to ensure legal certainty, fairness, and benefits for investors in the Indonesian capital market.